2019
DOI: 10.1111/vru.12791
|View full text |Cite
|
Sign up to set email alerts
|

Administration of certain sedative drugs is associated with variation in sonographic and radiographic splenic size in healthy cats

Abstract: Ultrasonography and radiography are standard diagnostic tests for cats with suspected splenic disease, however published information on outside sources of variation are currently lacking. The purpose of this prospective, randomized, crossover group study was to evaluate effects of common sedative drugs on the sonographic and radiographic characteristics of the spleen in healthy cats. Fifteen healthy adult research cats were randomly assigned into one of three groups corresponding to different sequences of admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
3
14
1
Order By: Relevance
“…9 In a recent study, acepromazine, butorphanol, dexmedetomidine or a combination of midazolam and butorphanol or dexmedetomidine, butorphanol and ketamine were administered to 15 healthy adult research cats to determine the effect, if any, the five sedative drugs/drug combinations had on ultrasonographic splenic size. 7 All drugs were administered intravenously, with the exception of the final drug combination, which was given by intramuscular injection. Acepromazine was the only drug to result in a statistically significant increase in splenic size, with the effect lasting at least 2-3 h postsedation.…”
Section: Splenomegaly Focal Masses and Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In a recent study, acepromazine, butorphanol, dexmedetomidine or a combination of midazolam and butorphanol or dexmedetomidine, butorphanol and ketamine were administered to 15 healthy adult research cats to determine the effect, if any, the five sedative drugs/drug combinations had on ultrasonographic splenic size. 7 All drugs were administered intravenously, with the exception of the final drug combination, which was given by intramuscular injection. Acepromazine was the only drug to result in a statistically significant increase in splenic size, with the effect lasting at least 2-3 h postsedation.…”
Section: Splenomegaly Focal Masses and Lesionsmentioning
confidence: 99%
“…This is supported by a recent study that documented the presence of a visible splenic tail on lateral abdominal radiographs in 4/15 (27%) non-sedated healthy adult cats. 7 Thus, it may be helpful to interpret such a finding on a case-by-case basis in the context of the history and clinical examination to determine the likely significance, with a view to further investigation if considered appropriate.…”
Section: Imaging the Spleenmentioning
confidence: 99%
“…Additionally, hematocrit values in some cases may decrease by up to 30% after the administration of sedatives, especially dexmedetomidine, ketamine and acepro-mazine. 22,23 (Clinicians should also be aware of the potential for increased ultrasonographic and radiographic splenic measures after the administration of acepromazine; 22 and several drugs used during PSA may change echocar-diographic results, as discussed later. )…”
Section: Patient Assessment and Preparation Before Psamentioning
confidence: 99%
“…Fewer data exist in the cat when compared with the dog ( 6 , 7 ). The anatomical differences between the feline and canine spleen, most notably of which being splenic size and its subsequent capacity for blood storage, may lead to a difference in magnitude of measurable changes ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane anesthesia has been reported to mildly increase splenic size in healthy blood-donor cats ( 7 ). A recent study reported that intravenous administration of acepromazine is associated with splenic enlargement on radiographs and ultrasound in healthy cats ( 6 ). The same study also reported that intravenous dexmedetomidine, the combination of midazolam and butorphanol intravenously or the combination of dexmedetomidine, butorphanol, and ketamine intramuscularly did lead to an increase in splenic size on radiographs, albeit not significant on ultrasound ( 6 ).…”
Section: Introductionmentioning
confidence: 99%